Brazilian silk production: economic and sustainability aspects. (2017) - Giacomin, Alessandra Maria; Garcia, João Berdu; Zonatti, Welton Fernando; Silva-Santos, Marcia Cristina; Laktim, Mariana Costa; Baruque-Ramos, Julia
Abstract: Brazil is the largest producer of silk cocoons on a commercial scale in the West, and the fifth largest producer of silk yarn in the world. The rearing of silkworm ( Bombyx mori ) is an activity developed mainly in small rural areas, where family work predominates and it represents an important income alternative. The aim of this study is to focus on economical and environmental issues of silk production in Brazil and it presents some uses of silk residues (by-products) in fashion and decoration sectors. Many applications for silk residues are possible, reducing the disposal of raw materials and consequently, the environmental impacts, besides generating employment and income. Thus, sericulture is very important for the Brazilian economy as well as in other developing countries, as it generates income for the country and for rural families, contributing to the settlement of people in these regions, and resulting in a positive correlation between silk production and the reduction of the carbon footprint considering the mitigation provided by mulberry trees.